1989
DOI: 10.1136/jmg.26.3.202
|View full text |Cite
|
Sign up to set email alerts
|

Limb anomalies in the CHARGE association.

Abstract: Clinical examinationBirth weight 2370 g (between 25th and 50th centile), length 49 cm (97th centile), and head circumference 31-5 cm (25th centile). Right iris coloboma, anteverted nostrils, long philtrum, moderate retrognathia, and low set, posteriorly rotated ears with preauricular pits bilaterally (fig 1). Choanal atresia bilaterally and narrow palate resulting

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
1

Year Published

1997
1997
2016
2016

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 5 publications
0
13
1
Order By: Relevance
“…Sixty-four patients (37.2%) had at least one limb anomaly (Table I) [Angelman, 1961;Ho et al, 1975;Rabaeus et al, 1983;Warburg, 1983;Bergstrom and Owens, 1984;Koletzko and Majewski, 1984;Dobrowski et al, 1985;Klein et al, 1985;Siebert et al, 1985;Davenport et al, 1986;Goldson et al, 1986;Wright et al, 1986;Brown et al, 1987;Chestler and France, 1988;Meinecke et al, 1989;Harvey et al, 1991;Marín et al, 1991;Van Meter and Weaver, 1996;de Lonlay-Debeney et al, 1997;Murofushi et al, 1997;Prasad et al, 1997;Dhooge et al, 1998;Kumar et al, 1999;Al Shamsan et al, 2000;Feigl et al, 2000;Haginomori et al, 2002;James et al, 2003]. The 64 patients had a total of 128 limb anomalies.…”
Section: Resultsmentioning
confidence: 96%
See 2 more Smart Citations
“…Sixty-four patients (37.2%) had at least one limb anomaly (Table I) [Angelman, 1961;Ho et al, 1975;Rabaeus et al, 1983;Warburg, 1983;Bergstrom and Owens, 1984;Koletzko and Majewski, 1984;Dobrowski et al, 1985;Klein et al, 1985;Siebert et al, 1985;Davenport et al, 1986;Goldson et al, 1986;Wright et al, 1986;Brown et al, 1987;Chestler and France, 1988;Meinecke et al, 1989;Harvey et al, 1991;Marín et al, 1991;Van Meter and Weaver, 1996;de Lonlay-Debeney et al, 1997;Murofushi et al, 1997;Prasad et al, 1997;Dhooge et al, 1998;Kumar et al, 1999;Al Shamsan et al, 2000;Feigl et al, 2000;Haginomori et al, 2002;James et al, 2003]. The 64 patients had a total of 128 limb anomalies.…”
Section: Resultsmentioning
confidence: 96%
“…Familial CHARGE patients, and patients with CHARGE phenotype with an abnormal karyotype were excluded. A total of 172 patients were included for study [Angelman, 1961;Edwards et al, 1961;Stool and Kemper, 1968;Buckfield et al, 1971;Levin et al, 1973;Ho et al, 1975;Sekhar and Sachs, 1976;Hittner et al, 1979;August et al, 1983;Curatolo et al, 1983;Rabaeus et al, 1983;Warburg, 1983;Bergstrom and Owens, 1984;Koletzko and Majewski, 1984;Dobrowski et al, 1985;Kaplan, 1985;Klein et al, 1985;Pardo and Chua, 1985;Siebert et al, 1985;Davenport et al, 1986;Goldson et al, 1986;Wright et al, 1986;Brown et al, 1987;Guyot et al, 1987;Stewart et al, 1987;Chestler and France, 1988;Coniglio et al, 1988;Ivarsson et al, 1988;Peters and Pontz, 1988;Wood et al, 1988;Allouche et al, 1989;Meinecke et al, 1989;Bartik et al, 1990;Ghalili et al, 1990;Menenzes and Coker, 1990;Harvey et al, 1991;Marín et al, 1991;Giorgetti et al, 1992;Venetikidou, 1993;…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Limb anomalies were not initially described in CHARGE syndrome [4]. Recently, limb anomalies have been reported as a rare manifestation in CHARGE syndrome [3,17,19]. On the other hand, Brock et al [4] reported that limb anomalies occurred in about 30% of patients with definite or probable CHARGE syndrome.…”
Section: Discussionmentioning
confidence: 96%
“…The reported cases are summarized in Table 1 (Meinecke et al, 1989;Blake and Prasad, 2006;Jongmans et al, 2006;Douglas and Lam, 2010).…”
Section: Discussionmentioning
confidence: 98%